History of the molecular chaperone concept: roles in assembly processes - Ellis, R. John (Henry Stewart Talks, 2007)
Definition of protein self-assembly and aggregation, First use of the term 'molecular chaperone', Nucleoplasmin, Chloroplast rubisco aggregation, The chaperonins, The general chaperone concept, Definition of 'molecular chaperone', The chaperone function, Protein folding on polysomes, Macromolecular crowding, Folding and assembly chaperones, Nuclear chaperones, Nucleosome assembly, Mechanism of nucleoplasmin action, The rubisco assembly chaperone RbcX